Influência da ocitocina hipocampal, durante a aquisição, consolidação e evocação de uma memória aversiva em ratas - Melo, João Eduardo Conceição (2024)
The study of memory made it possible to understand the mechanisms involved in its formation, in addition to enabling inferences about its modulations in the treatment of psychopathologies. Among the treatments, pharmacological modulation stands out, given the possibility of altering the neurophysiology of memory and fear. From this perspective, the hormone oxytocin has gained prominence for causing behavioral changes when faced with aversive stimuli. Therefore, our objective was to evaluate the influence of hippocampal oxytocin during the formation of an aversive memory in rats. For this, we used female Wistar animals. These underwent stereotactic surgery to allocate cannulas with two days of absolute rest after the procedure and another five days of monitoring the estrous cycle and after that they were evaluated in the modified plus maze task. The study was divided into four experiments, with two groups each [Control (CTL) and oxytocin (OXY)] that received a single administration of oxytocin or vehicle solution (0.5 uL of the substance per hemisphere in the hippocampus [2 µg/µL ]). In the first experiment, administration occurred 20 minutes before the training phase, in the second it occurred exactly after the training phase, in the third it was carried out 20 minutes before the test and in the fourth experiment, similar to the first, oxytocin or vehicle 20 was administered. minutes before training, but after 1 hour the animals were perfused to perform immunoreactivity for C-fos. Our results revealed that in experiment 1, OXY showed a decrease in learning the task in the training phase compared to CTL, exploring the aversive arm more (p=0.04), in addition to spending more time learning the task (p5=0.006 for OXY and p3=0.03 for CTL). We also saw that group OXY in the 3 experiments showed a decrease in the aversive response compared to CTL, given the no difference in remaining in the aversive arm compared to the safe one in the test phase, while CTL continued to avoid the aversive arm [CTL: p=0.002 , p=0.008, p=0.04 (experiments 1, 2 and 3 respectively). We also saw that in experiment 1, oxytocin favored coping with aversive situations, given the longer time spent in the aversive arm during training compared to CTL (p=0.04), similar to what was seen in experiment 3 in the test phase (p< 0.0001). In motor activity, no changes were observed in the parameter. In the C-fos analysis, we found that in the CA3 and dentate gyrus regions of the hippocampus it was possible to verify the effect of oxytocin treatment on the increase in immunoreactivity (p=0.03 and p=0.01 respectively), in addition to the anterior cingulate cortex also with an increase (p=0.04) and central amygdala that showed a decrease in the parameter for OXY animals (p=0.04). For the CA1 region, basolateral amygdala, prelimbic and infralimbic cortex, there was no effect of treatment on immunoreactivity (p=0.07, p=0.36, p=0.37 and p=0.07 respectively). The present study highlights the effects of oxytocin administration in reducing aversive responses. The findings of the present work suggest that oxytocin can modulate the limbic system, providing a better understanding of how it functions in relation to aversive memories.